Exhaust gas purification catalyst
By designing a catalytic layer with a specific structure in the exhaust purification catalyst, combining Rh and Pd-supported carrier particles, the problem of insufficient low-temperature purification activity and high-temperature oxygen storage capacity is solved, and a more efficient exhaust purification effect is achieved.
Patent Information
- Application Number
- JP2023145859
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-21
AI Technical Summary
The existing exhaust purification catalysts have insufficient purification activity under low temperature conditions and insufficient oxygen storage capacity (OSC) at high temperatures, making it difficult to meet increasingly stringent exhaust standards such as Euro7.
An exhaust purification catalyst is designed, which includes a matrix and a catalytic layer, consisting of a lower and upper catalytic layers. The lower catalytic layer contains Rh-supported carrier particles, while the upper catalytic layer upstream of the exhaust flow direction contains Pd-supported carrier particles, and the D50 particle size of the powder material of the two layers is between 6 μm and 10 μm.
By increasing low-temperature purification activity and ensuring adequate oxygen storage capacity, meeting increasingly stringent exhaust standards, especially at high temperature conditions.
Smart Images

Figure 2025039073000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an exhaust gas purifying catalyst comprising a substrate and a catalyst layer provided on the substrate. [Background technology]
[0002] Exhaust gas discharged from an internal combustion engine of an automobile or the like contains harmful components such as HC (hydrocarbon), CO (carbon monoxide), and NOx (nitrogen oxides). In order to remove these harmful components from exhaust gas, an exhaust gas purification catalyst is used, which includes a substrate and a catalyst layer provided on the substrate, and the catalyst layer includes a powdered carrier, an OSC material (oxygen storage material), and a powder material and catalytic metal particles supported on the carrier. Examples of the catalytic metal include Pt (platinum), Pd (palladium), and Rh (rhodium). Among the catalytic metals, Pd, which has high purification performance for HC and CO and high thermal stability, contributes greatly to the low-temperature purification activity of the exhaust gas purification catalyst at the start of operation of the internal combustion engine. On the other hand, in the exhaust gas purification catalyst, it is necessary to ensure sufficient OSC (Oxygen Storage Capacity) in order to mitigate the fluctuation of the oxygen concentration in the exhaust gas and improve the purification performance, especially at high temperatures. From these viewpoints, various technologies have been developed. For example, Patent Document 1 describes a purification device that includes a catalyst layer including a downstream catalyst layer and an upstream catalyst layer, in which the upstream catalyst layer and the downstream catalyst layer each include a lower layer containing Rh and an upper layer containing Pd, in which the length of the upstream catalyst layer is 30% or more and 70% or less of the total length of the substrate, and the Pd loading density of the upstream upper layer is more than 1 time and less than 3 times that of the downstream upper layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-055628 Summary of the Invention [Problem to be solved by the invention]
[0004] With the introduction of exhaust gas regulations such as Euro 7, the low-temperature purification activity of exhaust gas purification catalysts is becoming increasingly important. As a method for improving low-temperature purification activity, it is possible to use the warming up of the catalyst by the oxidation reaction of HC and CO with Pd, which contributes greatly to low-temperature purification activity. For example, as described in Patent Document 1, by arranging a layer containing Pd on the upper side of the catalyst layer and a layer containing Rh on the lower side, the frequency of contact of exhaust gas with the layer containing Pd can be increased, thereby improving the warming up of the catalyst and improving the low-temperature purification activity. On the other hand, in this case, the frequency of contact of exhaust gas with the layer containing Rh is reduced, so that the function of the OSC material may not be fully exerted. Therefore, there is a possibility that the OSC may be insufficient, especially at high temperatures.
[0005] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide an exhaust gas purification catalyst capable of improving low-temperature purification activity and ensuring a sufficient OSC. [Means for solving the problem]
[0006] In order to solve the above-mentioned problems, the present invention provides a catalyst for purifying exhaust gas, which comprises a substrate and a catalyst layer provided on the substrate, the catalyst layer having a lower catalyst layer provided on the substrate and an upper catalyst layer provided on the lower catalyst layer, the lower catalyst layer including a powder material containing a powder-like carrier and catalytic metal particles containing Rh supported on the carrier, the upper catalyst layer including an upstream catalyst layer disposed on the upstream side in the flow direction of exhaust gas and a downstream catalyst layer disposed on the downstream side in the flow direction of exhaust gas, at least the upstream catalyst layer of the upstream catalyst layer and the downstream catalyst layer including a powder material containing a powder-like carrier and catalytic metal particles containing Pd supported on the carrier, a cumulative 50% particle size D in a volume-based particle size distribution of the powder material included in at least the upstream catalyst layer of the upstream catalyst layer and the downstream catalyst layer 50 is characterized by being 6 μm or more and 10 μm or less. Effect of the Invention
[0007] According to the present invention, it is possible to improve the low-temperature purification activity and ensure a sufficient OSC. [Brief description of the drawings]
[0008] [Figure 1] 1 is a schematic perspective view of an exhaust gas purification catalyst according to a first embodiment. [Diagram 2] 2 is a schematic cross-sectional view showing a cross section parallel to the extending direction of cells of the exhaust gas purifying catalyst shown in FIG. 1. [Diagram 3] Graph (a) shows the relationship between D50 of the mixed powder of the upstream catalytic layer and the downstream catalytic layer of the upper catalytic layer, and Cmax and NOx-T50. Graph (b) shows the relationship between the weight percentage of Pd particles in the upstream catalytic layer, and Cmax and NOx-T50. [Figure 4] 13A is a graph showing the relationship between the coat width of the upstream catalytic layer of the upper catalytic layer and Cmax and NOx-T50, and FIG. 13B is a graph showing the relationship between the combination of D50 of the mixed powder of the upstream catalytic layer and the downstream catalytic layer of the upper catalytic layer and Cmax and NOx-T50. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the exhaust gas purification catalyst of the present invention will be described. Hereinafter, "upstream side" and "downstream side" refer to the upstream side and downstream side in the flow direction of exhaust gas, respectively. "Axial direction" refers to the axial direction of the substrate. "Stretching direction" refers to the stretching direction of the partition walls and cells, i.e., the direction in which the upstream side and the downstream side face each other, and is substantially the same as the axial direction.
[0010] First, the outline of the embodiment will be described by taking the first embodiment as an example. FIG. 1 is a schematic perspective view of the exhaust gas purifying catalyst according to the first embodiment. FIG. 2 is a schematic cross-sectional view showing a cross section parallel to the extension direction of the cells of the exhaust gas purifying catalyst shown in FIG. 1, and an enlarged cross-sectional view of the upstream catalyst layer of the upper catalyst layer of the catalyst layer is also shown. As shown in FIGS. 1 and 2, the exhaust gas purifying catalyst 1 according to the first embodiment is a so-called straight flow type three-way catalyst. The exhaust gas purifying catalyst 1 includes a honeycomb substrate 10 (substrate) and a catalyst layer 20 provided on the honeycomb substrate 10. The honeycomb substrate 10 is a substrate in which a cylindrical frame 11 and partition walls 14 that divide the space inside the frame 11 into a honeycomb shape are integrally formed. The partition walls 14 are porous bodies that define a plurality of cells 12 extending from the upstream end face 10Sa to the downstream end face 10Sb of the honeycomb substrate 10. The partition wall 14 includes a plurality of wall portions 14A arranged parallel to and spaced from each other so that a cross section perpendicular to the extension direction of the plurality of cells 12 is a square, and a plurality of wall portions 14B arranged parallel to and spaced from each other, perpendicular to the plurality of wall portions 14A. This makes the cross section perpendicular to the extension direction of the partition wall 14 have a lattice shape. The plurality of cells 12 are adjacent to each other with the partition wall 14 therebetween, and their upstream ends 12a and downstream ends 12b are open.
[0011] As shown in FIG. 2, the catalyst layer 20 has a lower catalyst layer 30 and an upper catalyst layer 40. The lower catalyst layer 30 is provided on a surface 14s of the partition wall 14 on the cell 12 side in a region from the upstream end of the partition wall 14 to the downstream end along the extension direction. The upper catalyst layer 40 is provided on a surface 30s of the lower catalyst layer 30 in a region from the upstream end of the partition wall 14 to the downstream end along the extension direction. The ratio of the length of the lower catalyst layer 30 in the extension direction (axial direction) to the length of the partition wall 14 in the extension direction (axial length of the substrate) is 100%. Although not shown, the lower catalyst layer 30 includes a powdered carrier composed of carrier particles, a powdered promoter-containing powdered material composed of promoter particles, and catalytic metal particles containing Rh (rhodium) supported on the carrier particles. The carrier particles of the powdered carrier include carrier particles containing an OSC material and carrier particles not containing an OSC material. The promoter particles of the powdered promoter do not support catalytic metal particles, and include promoter particles containing an OSC material and promoter particles not containing an OSC material.
[0012] The upper catalyst layer 40 has an upstream catalyst layer 40a arranged on the upstream side in the flow direction of the exhaust gas and a downstream catalyst layer 40b arranged on the downstream side in the flow direction of the exhaust gas. The upstream catalyst layer 40a extends from the upstream end of the partition wall 14 along the extension direction to a predetermined position downstream at a distance of 50% of the length of the partition wall 14 in the extension direction, and the downstream catalyst layer 40b extends from the downstream end of the partition wall 14 along the extension direction to the predetermined position. The ratio of the length of the upstream catalyst layer 40a in the extension direction (axial direction) to the length of the partition wall 14 in the extension direction (axial length of the substrate) is 50%. The ratio of the length of the downstream catalyst layer 40b in the extension direction to the length of the partition wall 14 in the extension direction is 50%. As shown in the enlarged view of FIG. 2, the upstream catalyst layer 40a and the downstream catalyst layer 40b contain a powdered carrier composed of carrier particles 2, a powdered promoter-containing powder material composed of promoter particles 6, and catalytic metal particles 4 containing Pd (palladium) supported on the carrier particles 2. The carrier particles 2 of the powdered carrier contain carrier particles containing an OSC material and carrier particles not containing an OSC material. The promoter particles 6 of the powdered promoter do not support catalytic metal particles 4, and contain promoter particles containing an OSC material, promoter particles not containing an OSC material, and promoter particles containing Ba sulfate. The cumulative 50% particle size D in the volumetric particle size distribution of the powdered material contained in the upstream catalyst layer 40a is 50 The diameter of the powder material contained in the downstream catalyst layer 40b is 6.5 μm. 50 Similarly, the diameter of the catalytic metal particles contained in the upstream catalytic layer 40a is 6.5 μm. The ratio of the weight of the catalytic metal particles contained in the upstream catalytic layer 40a to the weight of the catalytic metal particles contained in the upper catalytic layer 40 is 75% by weight.
[0013] In the exhaust gas purifying catalyst 1 according to the first embodiment, the D of the powder material contained in the upstream side catalytic layer 40a and the downstream side catalytic layer 40b of the upper catalytic layer 40 is 50By making the diameter of the pores in these layers 6 μm or more, the size of the pores in these layers can be made larger than that in the case where these layers are formed using a slurry containing an organic resin pore-forming material as in the conventional method. As a result, the exhaust gas can pass through the upstream catalyst layer 40a and the downstream catalyst layer 40b more easily than that in the case where a slurry containing an organic resin pore-forming material is used. This further increases the frequency of contact of the exhaust gas with the upstream catalyst layer 40a and the downstream catalyst layer 40b containing Pd, thereby increasing the warm-up effect due to the oxidation reaction of HC and CO in Pd, and improving the warm-up performance of the catalyst 1. In addition, by suppressing the decrease in the frequency of contact of the exhaust gas with the lower catalyst layer 30 containing Rh, the function of the OSC material can be fully exerted. Therefore, the low-temperature purification activity can be improved, and the OSC can be sufficiently secured, especially at high temperatures. On the other hand, the D of the powder material contained in the upstream catalyst layer 40a and the downstream catalyst layer 40b can be increased. 50 Since the thickness is 10 μm or less, these layers can be made thin. Therefore, the increase in pressure loss can be suppressed. When the upstream catalyst layer 40a and the downstream catalyst layer 40b are formed using a slurry containing an organic resin pore-forming material, when the substrate is fired after the slurry is applied, heat is generated due to the combustion of the pore-forming material, which generates thermal stress. In contrast, in the catalyst 1, these layers can be formed without adding a pore-forming material to the slurry, so that the generation of thermal stress can be suppressed. This avoids the durability problem, and various types of substrates with thin components can be used as the substrate 10, improving the warm-up property of the catalyst 1.
[0014] In addition, by making the ratio of the weight of the catalytic metal particles contained in the upstream catalytic layer 40a to the weight of the catalytic metal particles contained in the upper catalytic layer 40 50% by weight or more, the density of Pd in the upstream catalytic layer 40a, where the temperature is relatively high, becomes high, and the warm-up action by the oxidation reaction of HC and CO in Pd becomes even greater. Therefore, the warm-up property of the catalyst 1 can be effectively improved, and the low-temperature purification activity can be further improved. On the other hand, by making the ratio of the weight to be 90% by weight or less, the density of Pd in the downstream catalytic layer 40b is not too small, so that the function of the OSC material contained in the downstream catalytic layer 40b and the downstream region of the lower catalytic layer 30 can be fully exerted, and the OSC can be further sufficiently secured. Furthermore, by making the ratio of the length in the extension direction of the upstream catalytic layer 40a to the length in the extension direction of the partition wall 14 30% or more, the density of Pd in the downstream catalytic layer 40b is not too small, and the OSC can be further sufficiently secured. On the other hand, by making the ratio of the length in the extension direction of the upstream catalyst layer 40a to the length in the extension direction of the partition walls 14 70% or less, the density of Pd in the upstream catalyst layer 40a, where the temperature is relatively high, becomes high, so that the warm-up property of the catalyst 1 can be effectively improved and the low-temperature purification activity can be further improved. Next, the configuration of the exhaust gas purification catalyst according to the embodiment will be described in detail.
[0015] 1. Base material The substrate is not particularly limited, but may be, for example, a honeycomb substrate, etc. The material of the substrate is not particularly limited, but may be, for example, cordierite, etc.
[0016] 2.Catalyst layer The catalyst layer has a lower catalyst layer provided on the substrate and an upper catalyst layer provided on the lower catalyst layer. The catalyst layer is not particularly limited, but for example, when the substrate is a honeycomb substrate, the lower catalyst layer is provided on the cell side surface of the partition wall of the honeycomb substrate, and the upper catalyst layer is provided on the surface of the lower catalyst layer.
[0017] (1) Lower catalyst layer The lower catalyst layer includes a powder material containing a powdered support, and catalytic metal particles containing Rh (rhodium) supported on the support.
[0018] The powder material is not particularly limited as long as it contains a powdered carrier, but may further contain a powdered co-catalyst. The powdered carrier and the powdered co-catalyst are the same as the powdered carrier and the powdered co-catalyst contained in the upstream catalyst layer of the upper catalyst layer described later. When the powdered carrier material is of two or more types, or when the powdered carrier material is of one type and the powdered co-catalyst material is of one or more types, the powdered material is a mixed powder containing powders of two or more types of materials. The weight of the powdered material of the lower catalyst layer per 1 L of the volume of the coated part of the lower catalyst layer of the substrate is not particularly limited, but is preferably within a range of 30 g / L to 250 g / L, for example. The volume of the coated part of the substrate of the various catalyst layers refers to the volume of the axial region (coated part) of the substrate having the same axial length as the various catalyst layers (bulk volume including the net volume of the region and the volume of the internal cells). The catalytic metal particles are not particularly limited as long as they contain Rh. The average particle size of the catalytic metal particles is the same as that of the catalytic metal particles contained in the upstream catalyst layer of the upper catalyst layer described later. The weight of the catalytic metal particles of the lower catalytic layer per 1 L of the volume of the coating portion of the lower catalytic layer of the substrate is not particularly limited, but is preferably within a range of, for example, 0.05 g / L to 5 g / L. The lower catalytic layer is not particularly limited, but is preferably one that extends from the downstream end of the substrate (partition wall) along the axial direction (stretching direction) to a predetermined position away from the downstream end by a distance of 80% to 100% of the axial length of the substrate.
[0019] (2) Upper catalyst layer The upper catalytic layer has an upstream catalytic layer disposed upstream in the flow direction of the exhaust gas and a downstream catalytic layer disposed downstream in the flow direction of the exhaust gas. At least the upstream catalytic layer of the upstream catalytic layer and the downstream catalytic layer contains a powder material containing a powdered carrier and catalytic metal particles containing Pd (palladium) supported on the carrier. The cumulative 50% particle size D in the volumetric particle size distribution of the powder material contained in at least the upstream catalytic layer of the upstream catalytic layer and the downstream catalytic layer is 50 The cumulative 50% particle size D in the volumetric particle size distribution of the powder material is 6 μm or more and 10 μm or less. 50can be obtained by measuring, for example, a laser diffraction particle size distribution measuring device. The upper catalyst layer is not particularly limited, but it is preferable that both the upstream catalyst layer and the downstream catalyst layer contain the powder material and the catalytic metal particles. As the upper catalyst layer, the D 50 However, it is preferable that the thickness is 6 μm or more and 10 μm or less.
[0020] The powder material is not particularly limited as long as it contains a powdered support, and may further contain a powdered cocatalyst. The powdered support is composed of support particles that support catalytic metal particles. The material of the powdered support is not particularly limited, but examples thereof include Al 2 O 3 (Alumina), CeO 2 (Ceria), ZrO 2 (zirconia), and solid solutions thereof (for example, CZ composite oxide (ceria-zirconia composite oxide)), and two or more of these may be used. The powdered support material may not contain an OSC material, but is preferably one that contains an OSC material. The OSC material is not particularly limited, but may be CeO 2 , ZrO 2 , CZ composite oxide, etc. The powdered co-catalyst is composed of co-catalyst particles that do not support catalytic metal particles. The material of the powdered co-catalyst is not particularly limited, but in addition to the same material as the material of the powdered support, for example, Ba sulfate (BaSO 4 ) and sulfates of alkaline earth metals, and two or more of these may be used. When the powdered support material is of two or more types, or when the powdered support material is of one type and the powdered co-catalyst material is of one or more types, the powdered material is a mixed powder containing powders of two or more materials. In this case, D of the powdered material 50 D of mixed powder 50The weight of the powder material of the upstream catalyst layer per 1 L of the volume of the coating portion of the upstream catalyst layer of the substrate, and the weight of the powder material of the downstream catalyst layer per 1 L of the volume of the coating portion of the downstream catalyst layer of the substrate are not particularly limited, but are preferably within a range of 30 g / L or more and 250 g / L or less, for example.
[0021] The catalytic metal particles are not particularly limited as long as they contain Pd. The average particle size of the catalytic metal particles is, for example, 0.1 nm or more and 100 nm or less. The average particle size of the catalytic metal particles refers to the average particle size obtained by observing the catalytic layer with a TEM or the like. The upper catalytic layer is preferably one in which the ratio of the weight of the catalytic metal particles contained in the upstream catalytic layer to the weight of the catalytic metal particles contained in the upper catalytic layer is 50% by weight or more and 90% by weight or less. This is because the low-temperature purification activity can be further improved and the OSC can be further sufficiently secured. The catalytic metal particles contained in the upper catalytic layer refers to the total of the catalytic metal particles contained in the upstream catalytic layer and the catalytic metal particles contained in the downstream catalytic layer. The weight of the catalytic metal particles of the upstream catalytic layer per 1 L of the volume of the coated portion of the upstream catalytic layer of the substrate and the weight of the catalytic metal particles of the downstream catalytic layer per 1 L of the volume of the coated portion of the downstream catalytic layer of the substrate are not particularly limited, but are preferably within the range of, for example, 0.05 g / L or more and 5 g / L or less.
[0022] As the upper catalyst layer, the ratio of the axial length (stretching direction) of the upstream catalyst layer to the axial length of the substrate (length in the stretching direction of the partition wall) is preferably 30% or more and 70% or less. This is because the low-temperature purification activity can be further improved and the OSC can be further sufficiently ensured. As such an upper catalyst layer, it is particularly preferable that the upstream catalyst layer extends from the upstream end of the substrate (partition wall) along the axial direction (stretching direction) to a predetermined position downstream at a distance of 30% or more and 70% or less of the axial length of the substrate, and the downstream catalyst layer extends from the downstream end of the substrate along the axial direction to the predetermined position. EXAMPLES
[0023] EXAMPLES Hereinafter, the exhaust gas purifying catalyst according to the embodiment will be described more specifically with reference to examples and comparative examples.
[0024] 1. Raw materials for the substrate and catalyst layer of exhaust gas purification catalysts (1) Base material: 875cc (600 cells hexagonal, wall thickness 2mil) cordierite honeycomb substrate (2) Materials for the catalyst layer: a. Material 1 (Al 2 O 3 ): La 2 O 3 Composite Al 2 O 3 (La 2 O 3 : Powder containing particles of 1% to 10% by weight b. Material 2 (ACZ): Al 2 O 3 -CeO 2 -ZrO 2 Composite oxide (CeO 2 : Powder containing 15% to 30% by weight of particles (Nd 2 O 3 , La 2 O 3 , Y 2 O 3 (A small amount of ) is added to improve heat resistance. c. Material 3 (AZ): Al 2 O 3 -ZrO 2 Composite oxide (ZrO 2 : Powder containing particles of 50% to 80% by weight (Nd 2 O 3 , La 2 O 3 , Y 2 O 3 (A small amount of ) is added to improve heat resistance. d. Material 4 (Pyrochlore-type CZ composite oxide): 45wt%~55wt%-CeO 2 , 40wt%~50wt%-ZrO 2 , 1wt%~5wt%-Pr 6 O11 Powder containing composite oxide particles e. Material 5 (Ba sulfate): Powder containing barium sulfate particles f. Material 6 (Pd nitrate): Powder containing Pd nitrate particles g. Material 7 (Rh nitric acid): Powder containing particles of Rh nitrate h. Material 8 (Rh-loaded AZ): Powder containing AZ particles carrying Rh particles i. Material 9 (Pd-supported Al 2 O 3 ): Pd particles supported on Al 2 O 3 A powder containing particles of j. Material 10 (Pd-supported ACZ): Powder containing ACZ particles carrying Pd particles
[0025] 2. Preparation of exhaust gas purification catalyst [Comparative Example 1] (Formation of the lower catalyst layer of the catalyst layer) First, materials 7 and 3 were added to distilled water while stirring, and then dried and fired to prepare material 8. Next, materials 8, 1, 2, 4, and Al were added to distilled water while stirring. 2 O 3 The binder system was added and suspended to prepare slurry 1. At this time, the cumulative 50% particle size D in the volumetric particle size distribution of the mixed powder in which material 3 (powdered carrier), material 1 (powdered cocatalyst), material 2 (powdered cocatalyst), and material 4 (powdered cocatalyst) were mixed in slurry 1 was 50 (Cumulative 50% particle size D in the volumetric particle size distribution of the powder material contained in the lower catalyst layer 50 ) was adjusted to 5.0 μm.
[0026] Next, the slurry 1 was poured into the cells of the substrate from the downstream end, and unnecessary slurry was blown off with a blower to coat the surface of the cell side of the partition wall of the substrate with the material of the lower catalyst layer, thereby preparing the precursor layer of the lower catalyst layer. At that time, the weight of the material 7 converted into Rh was 0.25 g / L-zone, the weight of the material 1 was 30 g / L-zone, the weight of the material 2 was 60 g / L-zone, the weight of the material 3 was 30 g / L-zone, and the weight of the material 4 was 5 g / L-zone per 1 L of the volume of the coated portion of the lower catalyst layer of the substrate. In addition, the ratio of the length of the precursor layer of the lower catalyst layer in the extension direction (axial direction) to the length of the partition wall in the extension direction (axial direction length of the substrate) (hereinafter, sometimes abbreviated as "coat width of the lower catalyst layer") was 100%. Finally, the moisture was removed in a dryer maintained at 120°C for 2 hours, and then the substrate was baked in an electric furnace at 500°C for 2 hours to form a lower catalyst layer on the cell side surface of the partition walls of the substrate.
[0027] (Formation of the upstream catalyst layer of the upper catalyst layer of the catalyst layer) Next, Material 6, Material 1, Material 2, Material 5, and Al were added to the distilled water while stirring. 2 O 3 A system binder was added and suspended to prepare slurry 2. At this time, material 9 was prepared from material 6 and material 1, and material 10 was prepared from material 6 and material 2. The cumulative 50% particle size D in the volume-based particle size distribution of the mixed powder in which material 1 (powdered support), material 2 (powdered support), and material 5 (powdered cocatalyst) in slurry 2 were mixed was 50 (Cumulative 50% particle size D in the volumetric particle size distribution of the powder material contained in the upstream catalyst layer 50 ) was adjusted to 5.0 μm.
[0028] Next, the slurry 2 was poured into the cell of the substrate from the upstream end, and unnecessary parts were blown off with a blower, so that the surface of the lower catalyst layer was coated with the material of the upstream catalyst layer of the upper catalyst layer, and the precursor layer of the upstream catalyst layer was prepared. At that time, the weight of the Pd conversion of the material 6 was 2.25 g / L-zone, the weight of the material 1 was 25 g / L-zone, the weight of the material 2 was 75 g / L-zone, and the weight of the material 5 was 15 g / L-zone per 1 L of the volume of the coating part of the upstream catalyst layer of the substrate. In addition, the ratio of the length of the extension direction of the precursor layer of the upstream catalyst layer to the length of the extension direction of the partition wall (hereinafter, sometimes abbreviated as "coat width of the upstream catalyst layer") was 50%. Finally, the moisture was removed and calcination was performed in the same manner as in the formation of the lower catalyst layer, so that the upstream catalyst layer was formed on the surface of the lower catalyst layer.
[0029] (Formation of downstream catalytic layer of upper catalytic layer of catalytic layer) Next, Material 6, Material 1, Material 2, Material 5, and Al were added to the distilled water while stirring. 2 O 3 A system binder was added and suspended to prepare slurry 3. At this time, material 9 was prepared from material 6 and material 1, and material 10 was prepared from material 6 and material 2. The cumulative 50% particle size D in the volume-based particle size distribution of the mixed powder in which material 1 (powdered support), material 2 (powdered support), and material 5 (powdered cocatalyst) in slurry 3 were mixed was 50 (Cumulative 50% particle size D in the volumetric particle size distribution of the powder material contained in the downstream catalyst layer 50 ) was adjusted to 5.0 μm.
[0030] Next, the slurry 3 was poured into the cells of the substrate from the downstream end, and unnecessary parts were blown off with a blower, so that the surface of the lower catalyst layer was coated with the material of the downstream catalyst layer of the upper catalyst layer, and the precursor layer of the downstream catalyst layer was prepared. At that time, the weight of the Pd conversion of the material 6 was 0.75 g / L-zone, the weight of the material 1 was 25 g / L-zone, the weight of the material 2 was 75 g / L-zone, and the weight of the material 5 was 15 g / L-zone per 1 L of the volume of the coated part of the downstream catalyst layer of the substrate. In addition, the ratio of the length of the precursor layer of the downstream catalyst layer in the extension direction to the length of the partition wall in the extension direction (hereinafter, sometimes abbreviated as "coat width of the downstream catalyst layer") was 50%. Finally, the downstream catalyst layer was formed on the surface of the lower catalyst layer by removing moisture and baking in the same manner as when the lower catalyst layer was formed. In this way, a catalyst for exhaust gas purification was produced.
[0031] [Example 1] D of the mixed powder when preparing slurry 2 in the formation of the upstream catalyst layer of the upper catalyst layer of the catalyst layer 50 The D of the mixed powder was adjusted to 6.5 μm. 50 The particle size was adjusted to 6.5 μm. Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1. The exhaust gas purifying catalyst of Example 1 is an example of the exhaust gas purifying catalyst according to the first embodiment.
[0032] [Example 2] D of the mixed powder when preparing slurry 2 in the formation of the upstream catalyst layer of the upper catalyst layer of the catalyst layer 50 The D of the mixed powder was adjusted to 8.0 μm. 50 Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0033] [Example 3] D of the mixed powder when preparing slurry 2 in the formation of the upstream catalyst layer of the upper catalyst layer of the catalyst layer 50The D of the mixed powder was adjusted to 10.0 μm. 50 Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0034] [Comparative Example 2] D of the mixed powder when preparing slurry 2 in the formation of the upstream catalyst layer of the upper catalyst layer of the catalyst layer 50 The D of the mixed powder was adjusted to 12.0 μm. 50 Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0035] [Example 4] In the formation of the upstream catalyst layer of the upper catalyst layer of the catalyst layer, the amount of material 6 added when preparing the slurry 2 is reduced so that the weight of material 6 in terms of Pd per 1 L of the coating volume of the upstream catalyst layer of the substrate is 0.75 g / L-zone, and the D of the mixed powder is 50 In addition, in the formation of the downstream catalyst layer of the upper catalyst layer of the catalyst layer, the amount of material 6 added was increased when preparing the slurry 3, so that the weight of material 6 in terms of Pd per 1 L of the coating volume of the downstream catalyst layer of the substrate was 2.25 g / L-zone, and the D of the mixed powder was 50 Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0036] [Example 5] In the formation of the upstream catalyst layer of the upper catalyst layer of the catalyst layer, the amount of material 6 added is increased when preparing the slurry 2 so that the weight of material 6 in terms of Pd per 1 L of the coating volume of the upstream catalyst layer of the substrate is 2.70 g / L-zone, and the D of the mixed powder is 50In addition, in the formation of the downstream catalyst layer of the upper catalyst layer of the catalyst layer, the amount of material 6 added when preparing the slurry 3 was reduced so that the weight of material 6 in terms of Pd per 1 L of the coating portion of the downstream catalyst layer of the substrate was 0.30 g / L-zone, and the D of the mixed powder was 50 Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0037] [Example 6] In the formation of the upstream catalyst layer of the upper catalyst layer of the catalyst layer, the amount of material 6 added is increased when preparing the slurry 2 so that the weight of material 6 in terms of Pd per 1 L of the coating volume of the upstream catalyst layer of the substrate is 3.00 g / L-zone, and the D of the mixed powder is 50 In addition, in the formation of the downstream catalyst layer of the upper catalyst layer of the catalyst layer, the material 6 was not added when preparing the slurry 3, so that the weight of the material 6 in terms of Pd per 1 L of the coating portion of the downstream catalyst layer of the substrate was 0.00 g / L-zone, and the D of the mixed powder was 50 Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0038] [Example 7] In forming the upstream catalyst layer of the upper catalyst layer of the catalyst layer, the D of the mixed powder is used when preparing the slurry 2. 50 The thickness of the mixed powder was adjusted to 8.0 μm, and the coating width of the upstream catalyst layer was adjusted to 20%. 50 The thickness was adjusted to 8.0 μm, and the coating width of the downstream catalyst layer was 80%. Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0039] [Example 8] In forming the upstream catalyst layer of the upper catalyst layer of the catalyst layer, the D of the mixed powder is used when preparing the slurry 2. 50The thickness of the mixed powder was adjusted to 8.0 μm, and the coating width of the upstream catalyst layer was set to 35%. 50 The thickness was adjusted to 8.0 μm, and the coating width of the downstream catalyst layer was set to 65%. Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0040] [Example 9] In forming the upstream catalyst layer of the upper catalyst layer of the catalyst layer, the D of the mixed powder is used when preparing the slurry 2. 50 The thickness of the mixed powder was adjusted to 8.0 μm, and the coating width of the upstream catalyst layer was set to 65%. 50 The thickness was adjusted to 8.0 μm, and the coating width of the downstream catalyst layer was set to 35%. Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0041] [Example 10] In forming the upstream catalyst layer of the upper catalyst layer of the catalyst layer, the D of the mixed powder is used when preparing the slurry 2. 50 The thickness of the mixed powder was adjusted to 8.0 μm, so that the coating width of the upstream catalyst layer was 80%. 50 The thickness was adjusted to 8.0 μm, and the coating width of the downstream catalyst layer was set to 20%. Except for these points, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0042] [Example 11] D of the mixed powder when preparing slurry 2 in the formation of the upstream catalyst layer of the upper catalyst layer of the catalyst layer 50 Except for this, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0043] [Comparative Example 3] D of the mixed powder when preparing slurry 3 for forming the upper catalyst layer of the catalyst layer and the downstream catalyst layer 50Except for this, an exhaust gas purifying catalyst was produced in the same manner as in Comparative Example 1.
[0044] 3.Durability test A durability test was carried out on each of the exhaust gas purification catalysts of the comparative examples and examples using an actual engine. Specifically, each exhaust gas purification catalyst was attached to the exhaust system of a V8 engine, and exhaust gas in each of the stoichiometric and lean atmospheres was repeatedly passed through the catalyst bed at a catalyst bed temperature of 900°C for 50 hours for a certain period of time (ratio of 3:1).
[0045] 4.Performance Evaluation For each of the exhaust gas purification catalysts of the Comparative Examples and Examples that had been subjected to the durability test, a performance evaluation was carried out using an actual engine. Specifically, each exhaust gas purification catalyst was attached to the exhaust system of an L-type 4-cylinder engine, and the OSC (oxygen storage capacity), low-temperature purification activity, and pressure loss were evaluated as follows, and the relationship between the configuration of the exhaust gas purification catalysts of the Comparative Examples and Examples and their performance was investigated.
[0046] [OSC] Exhaust gas with an inlet gas temperature of 600°C and an A / F ratio of the inlet gas atmosphere fluctuating between 14.1 and 15.1 in a short cycle was supplied to each exhaust gas purification catalyst. In this case, the oxygen surplus or deficiency was calculated from the difference between the stoichiometric point and the A / F sensor output using the formula: OSC[g]=0.23×ΔA / F×injected fuel amount, and Cmax (maximum oxygen storage capacity)[g] was obtained. The results are shown in Table 1 below.
[0047] [Low temperature purification activity] For each exhaust gas purification catalyst, exhaust gas with an A / F of 14.4 in the inlet gas atmosphere was flowed at Ga=30g / s, while the inlet gas temperature was gradually increased from 200°C to 500°C. In this case, the NOx concentration of the inlet gas and the outlet gas was measured at each inlet gas temperature to calculate the NOx purification rate, and the inlet gas temperature at which 50% of the NOx was purified was measured as NOx-T50 (NOx 50% purification temperature) [°C]. The results are shown in Table 1 below.
[0048] [Pressure loss] For each of the exhaust gas purifying catalysts, the pressure loss was measured when air was caused to flow through the exhaust gas purifying catalyst.
[0049] [Table 1]
[0050] [Relationship between catalyst composition and performance] Based on the above performance evaluation results, for the exhaust gas purification catalysts of Examples 1 to 3 and Comparative Examples 1 and 2, the D of the mixed powder of the upstream catalyst layer (slurry 2) and the downstream catalyst layer (slurry 3) of the upper catalyst layer was 50 The relationship between the amount of the catalyst and Cmax and NOx-T50 was investigated. The results are shown in FIG. 3(a). Furthermore, for the exhaust gas purifying catalysts of Examples 1 to 3 and Comparative Examples 1 and 2, the D of the mixed powder of the upstream catalyst layer and the downstream catalyst layer of the upper catalyst layer was 50 As shown in Fig. 3(a), the relationship between the D of the mixed powder in the upstream catalyst layer and the downstream catalyst layer of the upper catalyst layer was investigated. 50 As the value of NOx-T50 increases, the value of Cmax increases and the value of NOx-T50 decreases. 50 When the diameter is 6 μm or more, it is believed that the effects of improving Cmax and reducing NOx-T50 can be sufficiently obtained. 50 The results of a survey on the relationship between pressure loss and D 50 It was found that when the particle size is 10 μm or less, the pressure loss can be suppressed to a level that ensures the marketability of the exhaust gas purification catalyst.
[0051] In addition, for the exhaust gas purifying catalysts of Examples 2 and 4 to 6, the relationship between the weight ratio of the Pd particles contained in the upstream catalytic layer to the weight of the Pd particles contained in the upper catalytic layer, and Cmax and NOx-T50 was investigated. The results are shown in FIG. 3(b). As shown in FIG. 3(b), as the weight ratio of the Pd particles in the upstream catalytic layer increases, NOx-T50 tends to decrease, and when the weight ratio of the Pd particles in the upstream catalytic layer is 90% by weight or less, Cmax is larger than when it is less than 90% by weight. When the weight ratio of the Pd particles in the upstream catalytic layer is 50% by weight or more and 90% by weight or less, it is considered that both the effect of improving Cmax and the effect of reducing NOx-T50 can be obtained at a high level. In addition, for the exhaust gas purifying catalysts of Examples 2 and 7 to 10, the relationship between the coat width of the upstream catalytic layer of the upper catalytic layer, Cmax and NOx-T50 was investigated. The results are shown in FIG. 4(a). As shown in FIG. 4(a), there was a tendency that Cmax increased as the coating width of the upstream catalytic layer increased, and NOx-T50 decreased as the coating width of the upstream catalytic layer decreased. When the coating width of the upstream catalytic layer was 30% or more and 70% or less, it was considered that both the effect of improving Cmax and the effect of reducing NOx-T50 were obtained at a high level. Furthermore, for the exhaust gas purification catalysts of Examples 2 and 11 and Comparative Example 3, the D of the mixed powder of the upstream catalytic layer and the downstream catalytic layer of the upper catalytic layer was 50 The relationship between the combination of the upstream catalyst layer and the Cmax and NOx-T50 was investigated. The results are shown in Figure 4(b). As shown in Figure 4(b), 50 In Example 2, the upstream catalyst layer D 50 Only the downstream catalyst layer is 8 μm thick. 50 In Example 11, the Cmax was larger and the NOx-T50 was lower than in Example 11, in which the D of the downstream catalyst layer was 5 μm. 50 Only the upstream catalyst layer is 8 μm thick. 50 The Cmax was larger and the NOx-T50 was lower than in Comparative Example 3, in which the diameter was 5 μm. 50 It is considered that the larger the value, the greater the contribution to improving Cmax and reducing NOx-T50.
[0052] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above-described embodiments, and various design modifications can be made without departing from the spirit of the present invention as described in the claims. [Explanation of symbols]
[0053] 1: exhaust gas purification catalyst, 10: honeycomb substrate, 12: cell, 14: partition wall, 20: catalyst layer, 30: lower catalyst layer, 40: upper catalyst layer, 40a: upstream catalyst layer, 40b: downstream catalyst layer
Claims
1. A catalyst for purifying exhaust gas comprising a substrate and a catalyst layer provided on the substrate, the catalyst layer includes a lower catalyst layer provided on the substrate and an upper catalyst layer provided on the lower catalyst layer, the lower catalyst layer includes a powder material containing a powdered support and catalytic metal particles containing Rh supported on the support; the upper catalytic layer has an upstream catalytic layer disposed on the upstream side in the flow direction of the exhaust gas and a downstream catalytic layer disposed on the downstream side in the flow direction of the exhaust gas, At least the upstream catalytic layer of the upstream catalytic layer and the downstream catalytic layer includes a powder material containing a powdered carrier and catalytic metal particles containing Pd supported on the carrier, A cumulative 50% particle size D in a volume-based particle size distribution of the powder material contained in at least the upstream catalytic layer of the upstream catalytic layer and the downstream catalytic layer 50 The catalyst for purifying exhaust gas is characterized in that the particle size is 6 μm or more and 10 μm or less.
2. 2. The exhaust gas purifying catalyst according to claim 1, wherein a ratio of a weight of the catalytic metal particles contained in the upstream catalytic layer to a weight of the catalytic metal particles contained in the upper catalytic layer is 50% by weight or more and 90% by weight or less.
3. 3. The exhaust gas purifying catalyst according to claim 1, wherein a ratio of an axial length of the upstream catalyst layer to an axial length of the substrate is 30% or more and 70% or less.
Citation Information
Patent Citations
Exhaust gas purification apparatus
JP2021055628A